Factors Affecting Eating Patterns on Blood Sugar Levels in Diabetes Mellitus Patients in UPT Puskesmas Narumonda - Betty Simanullang (Journal La Medihealtico, 2021)
The purpose of this research was to identify and evaluate the major dietary components linked with blood sugar levels in diabetic patients at UPT Puskesmas Narumonda in Toba Regency. This sort of study employs a cross-sectional descriptive analytic survey. The population in this research was 118 individuals, whereas the sample size was 54. Univariate, bivariate, and multivariate analyses were used to analyze the data. The chi-square test results indicate that the sugar level of people with diabetes mellitus is related to the number of calories p = 0.000, the type of food p = 0.000, and the eating schedule p = 0.003, indicating that there is a relationship between obesity, the number of calories, the type of food, and the eating schedule and blood sugar levels in people with diabetes mellitus. The findings of multivariate analysis indicate that the most relevant variable in this research, with an OR value of 53, is the quantity of calories. The research concluded that the quantity of calories consumed is the most important factor influencing blood sugar levels in persons with diabetes mellitus at UPT Puskesmas Narumonda, Toba Regency. To help lower the occurrence of diabetes mellitus, it is intended that the Health Service, puskesmas, and health professionals would collaborate to give frequent counseling about diabetes mellitus and a healthy and balanced diet.